2020
DOI: 10.21203/rs.3.rs-28756/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dexmedetomidine alleviates pulmonary edema through epithelial sodium channel (ENaC) via the PI3K/Akt/Nedd4-2 pathway in LPS- induced acute lung injury

Abstract: Background: Pulmonary edema is a hallmark in acute lung injury(ALI). Researchers have also revealed that dexmedetomidine (Dex) alleviate pulmonary edema following ALI, but the mechanism is unclear.The alveolar epithelial sodium channel (ENaC)-mediated alveolar fluid clearance (AFC) plays an important role in reducing pulmonary edema. In this study, we attempted to investigate the effect of Dex on ENaC in modulating AFC and its mechanism. Methods: LipopolysacchAride (LPS) was used to induce ALI in rat and alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
(39 reference statements)
3
2
0
Order By: Relevance
“…This study showed that administration of penehyclidine hydrochloride and dexmedetomidine during anesthesia for cardiac valve surgery reduced the impact of CPB, cardiac surgery and anesthesia on lung damage, increased OI, and reduced release of in ammatory factors and the occurrence and severity of PPCs, thus improving the prognosis of patients. This is consistent with the previously reported protective effects of penehyclidine hydrochloride and dexmedetomidine on lungs during cardiac surgery or other pathological conditions [11,12] . Our results showed that combination of penehyclidine hydrochloride and dexmedetomidine had a greater positive effect on the lungs than either of the two drugs alone.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study showed that administration of penehyclidine hydrochloride and dexmedetomidine during anesthesia for cardiac valve surgery reduced the impact of CPB, cardiac surgery and anesthesia on lung damage, increased OI, and reduced release of in ammatory factors and the occurrence and severity of PPCs, thus improving the prognosis of patients. This is consistent with the previously reported protective effects of penehyclidine hydrochloride and dexmedetomidine on lungs during cardiac surgery or other pathological conditions [11,12] . Our results showed that combination of penehyclidine hydrochloride and dexmedetomidine had a greater positive effect on the lungs than either of the two drugs alone.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the extubation time and length of ICU stay were shortened in the combination group. This supports the above results and analysis of changes in the levels of in ammatory factors, and is consistent with previous studies showing improvement of prognosis by single use of each drug [11] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A 2 ml of normal saline was instilled into the trachea and withdrew the BALF 30 . After centrifugation at 1200 g/min for 10 min, the BALF supernatant was stored at −80°C 31 . The cells sediment was immediately counted for total cells count and sorted cells count.…”
Section: Methodsmentioning
confidence: 99%